Correlation between bullying involvement and behavioral problems among adolescents - Panwar, Neha (International Journal of Research in Medical Sciences, 2023)
Background: Bullying is one of the common problems among adolescents. This study assessed the correlation between bullying involvement and behavioral problems among adolescents at selected schools of Dehradun, Uttarakhand. Methods: A quantitative correlational study was undertaken at selected school of Dehradun, Uttarakhand to assess the correlation between prevalence of bullying involvement and behavioral problems among 228 adolescents aged 12 to 17 years. The participants completed a self-report PRQ (peer relation questionnaire) to assess bullying involvement and SDQ (self report questionnaire) to assess behavioral problem. Results: The mean age of participants was 14.86. The prevalence of bullying involvement was 30.2%, from those 28 (9.7%) as bully, 59 (20.5%) as victim and 13 (4.5%) as bully-victim. There was significant correlation between bullying score and total difficulties problem (r=0.247); conduct problem (r=0.398); hyperactivity problem (r=0.143); peer problem (r=0.204) and pro-social problem (r=-0.215). There was significant correlation between victim score and total difficulties problem (r=0.309); emotional problem (r=0.328); conduct problem (r=0.289); peer problem (r=0.267) and pro social problem (r= -0.197). There was significant correlation between bully-victim score and total difficulties problem (r=0.341); emotional problem (r=0.258); conduct problem (r=0.420); hyperactivity problem (r=0.135); peer problem (r=0.288) and pro social problem (r=-0.250). Conclusions: Study showed that there is substantial prevalence of bullying involvement among adolescents. Bullying involvement is correlated to behavioral problem. Our findings can be used to construct school intervention directed toward bullying and behavioral problems.